1976
DOI: 10.2307/2441749
|View full text |Cite
|
Sign up to set email alerts
|

Gametophytes and Subgeneric Concepts in Lycopodium

Abstract: A critique of the Freeberg and Wetmore work on cultured'Lycopodium gametophytes of L. selago, L. [labelliiorme, and L. cernuum is presented. All three gametophytes are shown actually to be L. cernuum based on morphological and anatomical features of their sporophytes. A reassessment of characters in the genus demonstrates the taxonomic validity of the three groups proposed as subgenera within Lycopodium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Sexual and asexual life stages of L. a. are clearly separated: the gametophyte is subterranean and mycoparasitic (see Bruce, 1976) and may take more than 10 years to develop the sporophyte (Bruchmann, 1910;Oinonen, 1968). The sporophyte shows modular growth (Callaghan et al, 1986a, b) which, in the sense of White (1984), is also called metameric growth.…”
Section: Methodsmentioning
confidence: 99%
“…Sexual and asexual life stages of L. a. are clearly separated: the gametophyte is subterranean and mycoparasitic (see Bruce, 1976) and may take more than 10 years to develop the sporophyte (Bruchmann, 1910;Oinonen, 1968). The sporophyte shows modular growth (Callaghan et al, 1986a, b) which, in the sense of White (1984), is also called metameric growth.…”
Section: Methodsmentioning
confidence: 99%
“…However, in a recent morphological and anatomical study of material supplied by Freeberg, Bruce (1976) has demonstrated that the sporophytes found on the gametophytes identified as L. cornplanaturn and L. selago were identical with L. cernuum. Bruce (1976) concluded that all materials cultured by Freeberg and Wetmore (1957) were L. cernuurn and rejected the conclusion of Freeberg and Wetmore (1957) that the endophytic fungus was necessary for normal gametophytic development in L. cornplanaturn and L. selago. Given the results of Bruce's study (1976) and the above observations on garnetophytes of L. obscururn in axenic culture, it should be possible to grow normal gametophytes of L. cornplanaturn and L. selago without the endophytic fungus in axenic culture.…”
mentioning
confidence: 95%